Roles of leptin on energy balance and thermoregulation in Eothenomys miletus - Chen, Huibao; Zhang, Hao; Jia, Ting; Wang, Zhengkun; Zhu, Wanlong (Frontiers in Physiology, 2022)
Leptin is a hormone mainly synthesized and secreted by white adipose tissue (WAT), which regulates various physiological processes. To investigate the role of leptin in energy balance and thermoregulation in Eothenomys miletus, voles were randomly divided into leptin-injected and PBS-injected groups and placed at 25°C ± 1°C with a photoperiod of 12 L:12 D. They were housed under laboratory conditions for 28 days and compared in terms of body mass, food intake, water intake, core body temperature, interscapular skin temperature, resting metabolic rate (RMR), nonshivering thermogenesis (NST), liver and brown adipose tissue (BAT) thermogenic activity, and serum hormone levels. The results showed that leptin injection decreased body mass, body fat, food intake, and water intake. But it had no significant effect on carcass protein. Leptin injection increased core body temperature, interscapular skin temperature, resting metabolic rate, non-shivering thermogenesis, mitochondrial protein content and cytochrome C oxidase (COX) activity in liver and brown adipose tissue, uncoupling protein 1 (UCP1) content and thyroxin 5′-deiodinase (T45′-DII) activity in brown adipose tissue significantly. Serum leptin, triiodothyronine (T3), thyrotropin-releasing hormone (TRH) and corticotropin-releasing hormone (CRH) concentrations were also increased significantly. Correlation analysis showed that serum leptin levels were positively correlated with core body temperature, body mass loss, uncoupling protein 1 content, thyroxin 5′-deiodinase activity, nonshivering thermogenesis, and negatively correlated with food intake; thyroxin 5′-deiodinase and triiodothyronine levels were positively correlated, suggesting that thyroxin 5′-deiodinase may play an important role in leptin-induced thermogenesis in brown adipose tissue. In conclusion, our study shows that exogenous leptin is involved in the regulation of energy metabolism and thermoregulation in E. miletus, and thyroid hormone may play an important role in the process of leptin regulating energy balance in E. miletus.